A mixed-methods exploration of implementation of a comprehensive school healthy eating model one year after scale-up. Issue 5 (20th May 2015) - Naylor, Patti-Jean; McKay, Heather A; Valente, Maria; Mâsse, Louise C
Abstract: Objective: To study the implementation of a school-based healthy eating (HE) model one year after scale-up in British Columbia (BC). Specifically, to examine implementation of Action Schools! BC (AS! BC) and its influence on implementation of classroom HE activities, and to explore factors associated with implementation. Design: Diffusion of Innovations, Social Cognitive and Organizational Change theories guided our approach. We used a mixed-methods research design including focus group interviews (seven schools, sixty-two implementers) and a cross-sectional multistage survey to principals ( n 36, 92 % response rate) and teachers of grades 4 to 7 ( n 168, 70 % response rate). Self-reported implementation of classroom HE activities and reported use of specific AS! BC HE activities were primary implementation measures. Thematic analysis of focus group data and multilevel mixed-effect logistic regression analyses of survey data were conducted. Setting: Elementary schools across BC, Canada. Subjects: Thirty-nine school districts, thirty-six principals, 168 grade 4 to 7 teachers. Results: Forty-two per cent of teachers in registered schools were implementing AS! BC HE in their classrooms. Users were 6·25 times more likely to have delivered a HE lesson in the past week. Implementation facilitators were school champions, technical support and access to resources; barriers were lack of time, loss of leadership or momentum. Implementation predictors were teacher training, self-efficacy, experience with the physical activity component of AS! BC, supportive school climate and parental post-secondary education. Conclusions: Our findings reinforce that continued teacher training and support are important public health investments that contribute to successful implementation of school-based HE models after scale-up.